Use the principles of mathematical induction to prove `1/(1*2*3) + 1/(2*3*4) +1/(3*4*5)+...+1/(n(n+1)(n+2)) = (n*(n+3))/(4(n+1)(n+2))`

Expert Answers

An illustration of the letter 'A' in a speech bubbles

The relation `1/(1*2*3) + 1/(2*3*4) +1/(3*4*5)+...+1/(n(n+1)(n+2)) = (n*(n+3))/(4(n+1)(n+2))` has to be proved. This can be done using mathematical induction.

First take the base case n = 1: the right hand side is `1/(1*2*3) = 1/6` and the left hand side is also `(1*4)/(4*2*3) = 1/6`

Assume the relation holds for an integer n

=> `1/(1*2*3) + 1/(2*3*4) +1/(3*4*5)+...+1/(n(n+1)(n+2)) = (n*(n+3))/(4(n+1)(n+2))`

For the case of the integer n + 1,

`1/(1*2*3) + 1/(2*3*4) +1/(3*4*5)+...+1/(n(n+1)(n+2)) + 1/((n+1)(n+2)(n+3))`

=> `(n*(n+3))/(4(n+1)(n+2)) + 1/((n+1)(n+2)(n+3))`

=> `(n*(n+3)(n+3) + 4)/(4*(n+1)(n+2)(n+3))`

=> `(n*(n^2 + 6n + 9) + 4)/(4*(n+1)(n+2)(n+3))`

=> `(n^3 + 6n^2 + 9n + 4)/(4*(n+1)(n+2)(n+3))`

=> `((n+1)^2*(n+4))/(4*(n+1)(n+2)(n+3))`

=> `((n+1)(n+4))/(4*(n+2)(n+3))`

This proves the relation `1/(1*2*3) + 1/(2*3*4) +1/(3*4*5)+...+1/(n(n+1)(n+2)) = (n*(n+3))/(4(n+1)(n+2))` is true for all integral values.

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial